A methodology for shipping noise field calibration and excess noise estimation: the Azores case study - Jesus, Sergio (2022)
Economic globalization and the continuous search for food, energy and raw materials led to an estimated 3 dB/decade increase of ocean noise intensity. Determining the level of anthropogenic noise, the so-called excess noise, and building identifiable meaningful indicators for supporting marine management policies currently requires extensive observation data and computer modeling. For modeling purposes, in this study, anthropogenic noise was reduced to shipping traffic drawn from Automatic Identification System data, and environmental sound was attributed to surface wind only. Data-model comparison allowed introducing a methodology for simple model calibration and estimate excess noise. This methodology was tested on acoustic recordings performed in June 2018 at three locations to the southwest of Faial-Pico Islands in the Azores archipelago. The results show that field-calibrated excess noise sound maps are in line with the shipping distribution in the area, revealing a number of potentially marine life-threatening hotspots. Excess noise addresses the need for a quantifiable measure of ocean noise only and therefore offers a basis for building suitable continuous anthropogenic noise pollution indicators.